Contesti storici e radici teoriche della psicoterapia delle psicosi - De Simone, Gianfranco (Il sogno della farfalla, 2024)
On this issue we propose the introduction to the recently published collective volume, History of psychotherapy of psychosis (L’Asino d’oro edizioni, 2023). In this text, the author traces an overall overview of the history of the places and experiments through which psychotherapy of psychosis has developed since the nineteenth century. Despite the difference in clinical and cultural methods and approaches, what emerges is the shared challenge of understanding and treating severe mental illness, as opposed to any purely custodial perspective.